MODIFICĂRI INDUSE DE STRESUL HIDRIC, NUTRIŢIA MINERALĂ CU FOSFOR ŞI FIER ÎN CONŢINUTUL DE GLUCIDE ŞI AMINOACIZI LIBERI ÎN PLANTELE DE SOIA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2008)
An pot soil (cernoziom carbonated) culture experiment was conducted to determine the modification in carbohydrates and free amino acids content in soybean (cv. Zodiac) leaves in relation to phosphorus and iron nutrition under water stress conditions. Soybean plants were exposed to drought for 14 days during flowering stage of development and the samples were collected after stress period. The P-sufficient supply decreased the content of nonstructural carbohydrates (sucrose and hexose sugars) in leaves. This result was due to translocation of carbohydrates in sinks organs of roots and nodules. Iron supplemental nutrition with phosphorus fertilizer stimulated the accumulation of the level of free amino acids and soluble sugars irrespective of the level of soil moisture. Water shortage induced accumulation level of free amino acids in leaves. The both application phosphorus and iron increased the synthesis of amino acids in inoculated as well as in non-inoculated soybean plants. Hence the experimental data further emphasize the physiological importance of adequate nutrition with phosphorus and iron to attenuate the drought impact on plant metabolism and productivity.